Clinical Characteristics and Factors Associated With Disability and Impaired Quality of Life in Children With Juvenile Systemic Sclerosis: Results From the Childhood Arthritis and Rheumatology Research Alliance Legacy Registry. Issue 12 (8th November 2018) - Stevens, Brandi E.; Torok, Kathryn S.; Li, Suzanne C.; Hershey, Nicole; Curran, Megan; Higgins, Gloria C.; Moore, Katharine F.; Egla Rabinovich, C.; Dodson, Samuel; Stevens, Anne M.; ,
Abstract : Objective: To investigate clinical manifestations of juvenile systemic sclerosis (SSc; scleroderma), including disease characteristics and patient quality of life, using the multinational Childhood Arthritis and Rheumatology Research Alliance (CARRA) Legacy Registry. Methods: Patients with juvenile SSc were prospectively enrolled between 2010 and 2013. The diagnosis of juvenile SSc was determined by the enrolling pediatric rheumatologist, with the requirement for disease onset prior to age 18 years. Collected data included demographics, disease characteristics, medication exposure, and quality of life metrics. Results: In total, 64 patients with juvenile SSc were enrolled a median of 3.6 years after disease onset, which occurred at a median age of 10.3 years. The most common organ manifestations were dermatologic and vascular, followed by musculoskeletal, gastrointestinal, and pulmonary; in 38% of patients, ≥4 organ systems were affected. Patients with juvenile SSc had significantly more disability at enrollment compared with CARRA Legacy Registry patients with juvenile idiopathic arthritis, dermatomyositis, or systemic lupus erythematosus. Although physician‐reported measures correlated most closely with arthritis, dermatologic manifestations, and pulmonary manifestations, poor patient‐reported measures were associated with gastrointestinal involvement. During >50 person‐years of follow‐up, most organ manifestations remained stable, and no mortality or development of new solid organ involvement after enrollment was reported. Conclusion: In the first multicenter prospective cohort of patients with juvenile SSc in North America, the disease burden was high: multiorgan manifestations were common, and functional disability was greater than that observed in patients with other childhood‐onset rheumatic diseases. Gastrointestinal involvement had the greatest impact on quality of life.